Hepatic Innervations and Nonalcoholic Fatty Liver Disease - Adori, Monika; Bhat, Sadam; Gramignoli, Roberto; Valladolid-Acebes, Ismael; Bengtsson, Tore; Uhlèn, Mathias; Adori, Csaba (Seminars in Liver Disease, 2023)
Abbreviations graphical abstract: VMN/PVN, hypothalamic ventromedial nucleus/paraventricular nucleus; VLM/VMM, ventrolateral medulla/ventromedial medulla; SMG/CG, superior mesenteric ganglion/caeliac ganglia; NTS, nucleus of the solitary tract; NG, nodose ganglion.Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disorder. Increased sympathetic (noradrenergic) nerve tone has a complex role in the etiopathomechanism of NAFLD, affecting the development/progression of steatosis, inflammation, fibrosis, and liver hemodynamical alterations. Also, lipid sensing by vagal afferent fibers is an important player in the development of hepatic steatosis. Moreover, disorganization and progressive degeneration of liver sympathetic nerves were recently described in human and experimental NAFLD. These structural alterations likely come along with impaired liver sympathetic nerve functionality and lack of adequate hepatic noradrenergic signaling. Here, we first overview the anatomy and physiology of liver nerves. Then, we discuss the nerve impairments in NAFLD and their pathophysiological consequences in hepatic metabolism, inflammation, fibrosis, and hemodynamics. We conclude that further studies considering the spatial-temporal dynamics of structural and functional changes in the hepatic nervous system may lead to more targeted pharmacotherapeutic advances in NAFLD.
Keywords: nonalcoholic fatty liver disease; sympathetic nerves; parasympathetic nerves; noradrenaline; steatosis; inflammation; fibrosis; portal hypertension